Design, 3D printing, and preclinical validation of an extraglottic ramp to facilitate blind orotracheal intubation in emergency airway management - Jorman H. Tejada-Perdomo; Valentina Gutierrez-Perdomo; Juana V. Agudelo-Castro; Jorge A. Pérez-Gamboa; Alejandro Weinstein; Sebastián San Martín; Rodrigo Salas; Jorge A. Ramos-Castaneda (PLoS ONE, 2025)
The use of devices that facilitate rapid airway isolation is essential when managing critical patients in emergencies. In recent years, additive manufacturing has emerged as an innovative, versatile, and accessible technology for developing medical devices. This study presents the design, development, and validation of an extraglottic medical device created using computer-aided design tools and stereolithographic 3D printing to facilitate blind intubation by first responders. The device was iteratively modeled and fabricated with biocompatible materials; validation in airway simulators and human cadaveric specimens assessed dimensions, friction, intubation technique, and learning curve, and ease of use was rated with a Likert scale. Ten iterations led to a final design with low friction and minimal cervical manipulation; ramp angle, cup geometry, and distal tip were optimized for tube passage, and BioMed Flex 80A showed high strength and anatomical compatibility. The final version is a safe, reusable, and functional alternative for airway management and blind orotracheal intubation, particularly in emergencies and resource-limited settings; clinical validation in live patients is still needed.